2009
DOI: 10.1016/j.cub.2009.06.046
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Cos2 Homolog Kif7 Plays an Essential Role in Modulating Hh Signal Transduction during Development

Abstract: The Hedgehog (Hh) signaling pathway regulates development in animals ranging from flies to humans. Although its framework is conserved, differences in pathway components have been reported. A kinesin-like protein, Costal2 (Cos2), plays a central role in the Hh pathway in flies. Knockdown of a zebrafish homolog of Cos2, Kif7, results in ectopic Hh signaling, suggesting that Kif7 acts primarily as a negative regulator of Hh signal transduction. However, in vitro analysis of the function of mammalian Kif7 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
239
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(258 citation statements)
references
References 36 publications
15
239
1
3
Order By: Relevance
“…Kif7 physically interacts with Gli proteins to control their stability and proteolysis and can act as both a positive or negative regulator of Hh signal transduction. [8][9][10] Activation of the Hh pathway induces Kif7 localization from the base of the cilia to the tip, suggesting a possible function for Kif7 as a ciliary motor. 9 In contrast, Kif27 is indicated in regulating the construction of the central pair apparatus of motile 9 + 2 cilia by the recruitment of Fu.…”
Section: Trimming the Hedges: P53 Protective Functions In Cancermentioning
confidence: 99%
“…Kif7 physically interacts with Gli proteins to control their stability and proteolysis and can act as both a positive or negative regulator of Hh signal transduction. [8][9][10] Activation of the Hh pathway induces Kif7 localization from the base of the cilia to the tip, suggesting a possible function for Kif7 as a ciliary motor. 9 In contrast, Kif27 is indicated in regulating the construction of the central pair apparatus of motile 9 + 2 cilia by the recruitment of Fu.…”
Section: Trimming the Hedges: P53 Protective Functions In Cancermentioning
confidence: 99%
“…Taken together, these observations suggest Shh-induced phosphorylation of Smo is both necessary and sufficient to recruit Evc/Evc2, and the binding between Smo and Evc/Evc2 is mediated by Smo C-tail and is likely dependent on primary cilia. Several studies have shown that Kif7, the mammalian homolog of Drosophila Cos2, is involved in Hh signaling [24][25][26][27]. In Drosophila, Hh-induced Smo phosphorylation and conformational change promotes Smo/Cos2 association [20,21].…”
Section: Hh-induced Phosphorylation Of Smo Promotes Its Binding To Evmentioning
confidence: 99%
“…Activated Fu regulates both the activator and repressor form of Ci, likely by phosphorylating Cos2 and Sufu [18,[20][21][22][23]. Both Sufu and the mammalian homolog of Cos2, Kif7, are involved in Hh signaling [24][25][26][27][28]. By contrast, the mammalian homolog of Fu is not required for Hh signaling during development [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Downstream of Smo, the SuFu⅐Gli complex (likely with Kif7) also accumulates in the cilium (13)(14)(15), and Gli phosphorylation by PKA is somehow inhibited, preventing cleavage of Gli-FL into Gli-R. There, the SuFu⅐Gli complex dissociates via unknown mechanism(s) (16), thereby leading to the activation of Gli-FL into Gli-A, which can activate Hh target gene transcription in the nucleus.…”
mentioning
confidence: 99%